GIANT CELL MYOCARDITIS IN MODERN CLINICAL PRACTICE: GIANT CELL MYOCARDITIS - Ratko,; Djukanovic, Lazar; Zdravkovic, Marija; Lasica, Andjelka; Krljanac, Gordana; Polovina, Marija; Ristic, Arsen; Asanin, Milika (Medical Research, 2023)
Abstract:Gigant cell myocarditis is a rare but extremely severe disease with a frequent need for heart transplantation and a high mortality rate. To this day, the most common reason for the appearance of this disease has not been precisely determined, but its frequent association with autoimmune diseases speaks in favour of autoimmune etiology. Clinically, it is presented to the greatest extent by symptoms and signs of acute heart failure and ventricular rhythm disturbances, which are registered even in half of the patients. Arrhythmias can be accompanied by the appearance of palpitations, repeated syncope, and even sudden cardiac death. A severe degree of acute heart failure in hemodynamically unstable patents who respond inadequately to the applied therapy for heart failure and refractory heart rhythm disorders and/or conduction disorders that are common in these patients should always raise the suspicion that it is giant cell myocarditis. Given that changes in the electrocardiogram, echocardiography and positive biomarker values are not strictly specific for this disease, the diagnosis of gigant cell myocarditis is most often established by endomyocardial biopsy, especially in patients with a fulminant form of the disease. Timely endomyocardial biopsy enables not only quick and accurate diagnosis, but also early application of immunosuppressive therapy, which greatly improves the outcome of these patients. Pathohistological verification of this disease is important in order to rule out cardiac sarcoidosis and other granulomatous infectious and non-infectious diseases. Given that a large number of patients have a fulminant course of the disease, early and rapid diagnosis, application of inotropic stimulation and mechanical circulatory support in hemodynamically unstable patients and adequate modern therapeutic regimen can largely reduce the mortality of these patients, which is still high despite modern diagnostic and therapeutic progress of medicine.
Keywords: fulminant myocarditis, acute heart failure, hemodynamic instability, endomyocardial biopsy, mortality.